Artificial Neural Networks in Finance and Manufacturing 2006
DOI: 10.4018/978-1-59140-670-9.ch009
|View full text |Cite
|
Sign up to set email alerts
|

Improving Returns on Stock Investment through Neural Network Selection

Abstract: Artificial neural networks’ (ANNs’) generalization powers have in recent years received admiration of finance researchers and practitioners. Their usage in such areas as bankruptcy prediction, debt-risk assessment, and security-market applications has yielded promising results. With such intensive research and proven ability of the ANN in the area of security-market application and the growing importance of the role of equity securities in Singapore, it has motivated the conceptual development of this work in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…The results indicate that predictions can be produced to a high level of accuracy, in a readily understandable format. Quah [7] and Srinivasan uncover the intricate relationships between the performance of stocks and the related financial and technical variables by neural network. Experimental results obtained this far have been very encouraging.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that predictions can be produced to a high level of accuracy, in a readily understandable format. Quah [7] and Srinivasan uncover the intricate relationships between the performance of stocks and the related financial and technical variables by neural network. Experimental results obtained this far have been very encouraging.…”
Section: Introductionmentioning
confidence: 99%
“…Lee and Chen (2007) Wu and Xu (2006) found that fundamental analysis can be powerful to predict stock price, especially with the aid of neural networks approach and rough set theory. Atiya et al (1997), Quah and Srinivasan (1999), Raposo and Cruz (2002) also roped in fundamental indicators to forecast stock prices using Neural Networks. Schumaker and Chen (2006) tried to find out influence of news article on stock price using Support Vector Machine (SVM).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The learning process includes storing the presented data. All instances correspond to points in an n-dimensional space and the nearest neighbors of a given query that already defined regarding the standard Euclidean distance [8]. The probability of a query q belongs to a class c that can be calculated as follows:…”
Section: K-nn Based Classifiersmentioning
confidence: 99%